Are mental illnesses diseases of the brain? - Fuchs, Thomas (Critical neuroscience, 2012)
This chapter contains sections titled: Circular Causality of Living Systems Mental Illness as Circular Process Circular Causality in Pathogenesis Circular Causality in Therapy Conclusion References